A Study on Customers’ Expectations towards Purchase of Smartphones in India: with Reference to Andhra Pradesh, India - Srinivasa Rao Dokku; Rajesh C.; P. Adi Lakshmi (Annals of Management and Organization Research, 2022)
Purpose: The purpose of the research study is to determine Indian consumers' expectations regarding the purchase of cell phones. The survey addresses issues like what characteristics customers look for in a smartphone before purchasing a mobile phone, what the anticipated price of a smartphone is, etc. Research methodology: 250 respondents from Andhra Pradesh, India, were taken into account for the study utilizing Google forms. Excel and SPSS software were used to analyze the data. For the data analysis in the study, percentages and the chi-square test was utilized. Results: The use of smartphones has substantially increased recently. In the two years following their purchase, the majority of respondents in the selected location upgraded their smartphones. When buying new cell phones, the client prioritizes brand, pricing, camera, internal storage, and battery. The custodians prioritize using the internet to find information such as reviews, prices, models, and the availability of new models. According to the report, consumers anticipate paying less than Rs. 10,000 and expect a smartphone with 4GB RAM, a 48MP camera, 68GB of internal memory, and a battery that can hold more than 5000aMh. Limitations: The study has considered only 250 respondents by using Google Forms. Contribution: The study will assist the companies that make mobile devices in developing their pricing and other sales strategies as well as understanding how customers view the purchase of new mobile devices.